Light-controlled thrombin catalysis and clot formation using a photoswitchable G-quadruplex DNA aptamer. Issue 39 (26th April 2019) - Ali, Aysha; Bullen, Gemma A.; Cross, Benjamin; Dafforn, Timothy R.; Little, Haydn A.; Manchester, Jack; Peacock, Anna F. A.; Tucker, James H. R.
Abstract : The application of light distorts the structure of an anthracene-functionalized DNA aptamer, preventing its inhibitive binding to the clotting enzyme thrombin, resulting in photoswitched catalysis. Abstract : The reversible photocontrol of an enzyme governing blood coagulation is demonstrated. The thrombin binding aptamer (TBA ), was rendered photochromic by modification with two anthracene groups. Light-triggered anthracene photodimerisation distorts its structure, inhibiting binding of the enzyme thrombin, which in turn triggers catalysis and the resulting clotting process.